Activism in Architecture : Bright Dreams of Passive Energy Design. - McDonald, Margot; Dayer, Carolina (Milton : Routledge, 2018)
This edited collection gathers contributions from a diverse range of renowned scholars and professionals to uncover the unique relationship between passive architectural systems and activism. Focusing on the pioneering work of the influential American chemist and inventor, Harold R. Hay (1909-2009), and the environmental awareness events that took hold in the United States during the 1960s and 1970s, the book assembles essays which closely examine Hay's contribution to architecture and the work of those who directly and tangentially were affected by it. The book also offers insights into the role of passive energy design today. Appealing to researchers, architects and students interested in architecture and design technology, Activism in Architecture explores the role of passive environmental inventions as an active agent in shaping socio-political debates.
A validated methodology to predict the performance of Skytherm NorthThe superior performance of Skytherm North; The untapped genius of Harold R. Hay; Notes; Part III Necessity and pleasure; 12 Building experience; Responsive materials and systems; Situating; Programmable materials; Phase-change background; Adaptive architecture; Phase-change tiles; Prototypes and design process; On mass and transparency; Conclusion; Notes; 13 Thermal landscaping of buildings: Climate-proofing design; The thermal landscaping of buildings; Ways forward: suggestions for a new comfort code; Notes.
14 Resilience as a driver of passive design.
OCLC-licensed vendor bibliographic record.
Keywords: Hay, H. R. -- Influence; Architecture and society -- United States; Architecture and energy conservation -- United States; Solar energy -- Passive systems -- United States; Environmentalism -- United States; ARCHITECTURE -- Adaptive Reuse & Renovation; ARCHITECTURE -- Buildings -- Landmarks & Monuments; ARCHITECTURE -- Professional Practice; ARCHITECTURE -- Reference; ARCHITECTURE -- General; ARCHITECTURE -- Design & Drafting